Ternary Fe–Co–Mo alloys as catalytic materials in oxidations reactions of low molecular weight alcohols - Sachanova, Yu. I.; Sakhnenko, N. D.; Ved, M. V.; Yermolenko, I. Yu.; Volobuyev, M. N. (Київський національний університету технологій та дизайну, 2019)
The electrocatalytic properties of ternary Fe–Co–Mo alloys synthesized from complex Fe(III) – citrate electrolytes are discussed. The relationship between the composition and surface morphology of electrolytic alloys is considered. It was found that the optimal content of molybdenum in the alloy ranges from 12 to 18 at.%. The increase in the content of this component is not possible, since it can lead to cracking and wear of the surface due to the occurrence of internal stresses. The formation of the globular structure of the alloy Fe–Co–Mo is due to the presence of a refractory metal. The resulting alloys exhibit electrocatalytic activity in the oxidation reactions of methanol and ethanol, as evidenced by the high values of currents in the anodic and cathodic regions of cyclic voltammetric dependencies with maximum values at 0.56 V and 0.6 V, respectively. The course of adsorption of methanol and ethanol on the surface of the alloy Fe–Co–Mo has been established.
Тернарні сплави Fe–Co–Mo як каталітичні матеріали в реакціях окиснення низькомолекулярних спиртів
Keywords: molybdenum; complex citrate electrolytes; galvanic alloys; electrooxidation; electrocatalyst; fuel cell; альтернативні джерела енергії; електролітичні покриви; компоненти-аморфізатори; паливні елементи; метанол; електроокиснення